Architectural and urban development of the Romny Midtown in 12th – 19th centuries - Rybchynskyi, Oleh; Matiiva, Kateryna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
Based on the cartographic sources of the 17th – 19th centuries, the previous researches of historical and scientific literature, the historical development materials of the city of Romny have been analyzed and systematized. Based on the investigated material, the main stages of architectural and urban planning of Romny have been determined.